Accounting, Accountability and Society Trends and Perspectives in Reporting, Management and Governance for Sustainability - Del Baldo, Mara.; Dillard, Jesse; Baldarelli, Maria-Gabriella.; Ciambotti, Massimo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book addresses the growing interest among policymakers, practitioners and academics in the evolution and the future implications of social, environmental and sustainability accounting. To do so, it examines the conceptual and practical application of accountability at multiple levels and contexts, and presents a range of case studies focusing on salient issues, perspectives and the potential of multidimensional accounting and reporting regimes. Intended for a diverse audience, the book allows readers to gain a better understanding of the topics, encourages dialogue and debate, and stimulates innovation in scholarship, policy and practice. .
Accounting and accountability tools and practices for environmental issues: a narrative historical academic debate -- The management process underpinning the Non-financial reporting: a case study of a listed Italian company -- A Sociotechnical Analysis of Accounting for Employee Health and Safety: Evidence from a multiple case study -- Ethics, social responsibility and tax aggressiveness. Can a code of ethics absolve a company? -- Accounting for sustainability. Could cost accounting be the right tool? -- Mandatory disclosure of non-financial information: A structured Literature Review -- What drives the level of non-financial assurance in PIEs? Empirical evidence on the European firms listed on Forbes 2000 -- Review and Reflections.
Keywords: Social responsibility of business; Accounting; Business ethics; Corporate governance; Corporate Social Responsibility; Financial Accounting; Business Ethics; Corporate Governance